Conjugated Polymers Based on Difluorobenzoxadiazole toward Practical Application of Polymer Solar Cells. Issue 22 (11th September 2017) - Wang, Junyi; Wang, Shiliang; Duan, Chunhui; Colberts, Fallon J. M.; Mai, Jiangquan; Liu, Xi; Jia, Xiao'e; Lu, Xinhui; Janssen, René A. J.; Huang, Fei; Cao, Yong
Abstract: To advance polymer solar cells (PSCs) toward real‐world applications, it is crucial to develop materials that are compatible with a low‐cost large‐scale manufacturing technology. In this context, a practically useful polymer should fulfill several critical requirements: the capability to provide high power conversion efficiencies (PCEs) via low‐cost fabrication using environmentally friendly solvents under mild thermal conditions, resulting in an active layer that is thick enough to minimize defects in large‐area films. Here, the development of new photovoltaic polymers is reported through rational molecular design to meet these requirements. Benzodithiophene (BDT)‐difluorobenzoxadiazole (ffBX)‐2‐decyltetradecyl (DT), a wide‐bandgap polymer based on ffBX and BDT emerges as the first example that fulfills the qualifications. When blended with a low‐cost acceptor (C60 ‐fullerene derivative), BDT‐ffBX‐DT produces a PCE of 9.4% at active layer thickness over 250 nm. BDT‐ffBX‐DT devices can be fabricated from nonhalogenated solvents at low processing temperature. The success of BDT‐ffBX‐DT originates from its appropriate electronic structure and charge transport characteristics, in combination with a favorable face‐on orientation of the polymer backbone in blends, and the ability to form proper phase separation morphology with a fibrillar bicontinuous interpenetrating network in bulk‐heterojunction films. With these characteristics, BDT‐ffBX‐DT represents a meaningful step toward future everyday applications of polymer solar cells. Abstract : Two new conjugated polymers based on difluorobenzoxadiazole bring real‐world applications of polymer solar cells closer. They integrate multiple advantages including high power conversion efficiency built on low‐cost acceptors, allowing thick active layers, and processability from green solvents under mild conditions. Particularly, benzodithiophene‐difluorobenzoxadiazole‐2‐decyltetradecyl (BDT‐ffBX‐DT) is a champion in meeting a comprehensive list of prerequisites for future application of polymer solar cells.